Social Support and Hope Mediate the Relationship Between Gratitude and Depression Among Front-Line Medical Staff During the Pandemic of COVID-19 - Feng, Lijuan; Yin, Rong (Frontiers in Psychology, 2021)
Background: The pandemic of Coronavirus Disease 2019 (COVID-19) has burdened an unprecedented psychological stress on the front-line medical staffs, who are at high risk of depression. While existing studies and theories suggest that factors such as gratitude, social support and hope play a role in the risk of depression, few studies have combined these factors to explore the relationship between them. Objective: This study examined the mediating roles of social support and hope in the relationship between gratitude and depression among front-line medical staffs during the epidemic of COVID-19. Methods: This study used the Gratitude Questionnaire, the Perceived Social Support Scale, the State Hope Scale, the Center for Epidemiologic Studies Depression Scale to examine the gratitude, social support, hope and depression among 344 front-line medical workers in Wuhan, which was the hardest-hit area of COVID-19 in China. Results: The results showed that the prevalence of mild depressive disorder was 40.12% and the prevalence of major depressive disorder was 9.59% among front-line medical staffs during the epidemic of COVID-19; gratitude had a direct and negative effect on depression. Gratitude were negative predictors of depression through the mediating variables of social support and hope [βgratitude -social support -depression = -0.096, 95%CI(-0.129~-0.064); βgratitude -hope -depression =-0.034, 95%CI(-0.055~-0.013)], as well as via an indirect path from social support to hope [βgratitude -social support -hope -depression=-0.089, 95%CI (-0.108~-0.070)]. Conclusions: These findings suggested that during the epidemic of COVID-19, front-line medical staffs’ gratitude may have a negative relation with depression by social support and hope.